PENGENALAN DAN PEMANFAATAN MARKETPLACE E-COMMERCE UNTUK PELAKU UKM WILAYAH CILEGON - Wahyuni, Nuraida; Saeful Mutaqin S., Ade Irman; Gunawan, Akbar (Jurnal Pengabdian Dinamika, 2019)
The growth of Small and Medium Enterprises (SMEs), especially in the Cilegon region in 2017,increased significantly from the target of 2.5% with a realization of 7.48%. The increase is the result ofcoaching and training carried out by the Office of Cooperative Micro and Small Enterprises in Cilegoncity. On the other hand, the growth of the e-commerce marketplace in Indonesia in 2017 also saw asignificant increase. The problem that is often encountered is that good growth from SMEs has not beenaccompanied by the growth of the use of the existing e-commerce marketplace to keep pace with rapidinformation technology. The aim of this research is to introduce e-commerce marketplace in Indonesiaand utilize one of the e-commerce marketplace to help product marketing and expand market access.The method used in this research is survey method. The survey was conducted on three business actors.Research instruments in the form of direct interviews with business people. The information extractedis about the knowledge of business people about e-commerce marketplaces in Indonesia. Business actorsare given information about information technology in order to improve product marketing. The resultsobtained were from six business actors studied, there was one business actor who was familiar withmarketlace e-commerce. The business actors studied have not utilized the existing e-commercemarketplace and can be accessed for free. Business actors use one of the existing e-commercemarketplaces, such as Shopee.